Biomaterial Scaffolds as Pre‐metastatic Niche Mimics Systemically Alter the Primary Tumor and Tumor Microenvironment. Issue 10 (9th March 2018) - Aguado, Brian A.; Hartfield, Rachel M.; Bushnell, Grace G.; Decker, Joseph T.; Azarin, Samira M.; Nanavati, Dhaval; Schipma, Matthew J.; Rao, Shreyas S.; Oakes, Robert S.; Zhang, Yining; Jeruss, Jacqueline S.; Shea, Lonnie D.
Abstract: Primary tumor (PT) immune cells and pre‐metastatic niche (PMN) sites are critical to metastasis. Recently, synthetic biomaterial scaffolds used as PMN mimics are shown to capture both immune and metastatic tumor cells. Herein, studies are performed to investigate whether the scaffold‐mediated redirection of immune and tumor cells would alter the primary tumor microenvironment (TME). Transcriptomic analysis of PT cells from scaffold‐implanted and mock‐surgery mice identifies differentially regulated pathways relevant to invasion and metastasis progression. Transcriptomic differences are hypothesized to result from scaffold‐mediated modulations of immune cell trafficking and phenotype in the TME. Culturing tumor cells with conditioned media generated from PT immune cells of scaffold‐implanted mice decrease invasion in vitro more than two‐fold relative to mock surgery controls and reduce activity of invasion‐promoting transcription factors. Secretomic characterization of the conditioned media delineates interactions between immune cells in the TME and tumor cells, showing an increase in the pan‐metastasis inhibitor decorin and a concomitant decrease in invasion‐promoting chemokine (C‐C motif) ligand 2 (CCL2) in scaffold‐implanted mice. Flow cytometric and transcriptomic profiling of PT immune cells identify phenotypically distinct tumor‐associated macrophages (TAMs) in scaffold‐implanted mice, which may contribute to an invasion‐suppressive TME. Taken together, this study demonstrates biomaterial scaffolds systemically influence metastatic progression through manipulation of the TME. Abstract : Biomaterial implants that mimic the pre‐metastatic niche are shown to redirect immune and tumor cell populations in vivo. However, the systemic effects of pre‐metastatic niche mimics on metastasis progression have yet to be characterized. In this work, synthetic biomaterial implants were shown to systemically alter the primary tumor and the tumor microenvironment to promote an invasion‐suppressive phenotype.